Neighborhood outer split domination in graphs. (4th July 2019) - Prabha, K. Suriya; Amutha, S.; Anbazhagan, N.; Gomathi, S. Sankara
Abstract: A neighborhood outer split dominating set (nosd-set) in a graph G is a dominating set S with the property that the sub graph induced by the open neighborhood of the set S is disconnected. The minimum cardinality of vertices in such a set is called the neighborhood outer split domination number of G and it is denoted by γ n os . In this paper, we initiate a study of this parameter.